2019
DOI: 10.1021/acssensors.9b00778
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Self-Assembly of Ti3C2Tx MXene and Gold Nanorods as an Efficient Surface-Enhanced Raman Scattering Platform for Reliable and High-Sensitivity Determination of Organic Pollutants

Abstract: A reliable surface-enhanced Raman scattering (SERS) substrate composed of two-dimensional (2D) MXene (Ti 3 C 2 T x ) nanosheets and gold nanorods (AuNRs) is designed and fabricated for sensitive detection of organic pollutants. The AuNRs are uniformly distributed on the surface of the 2D MXene nanosheets because of the strong electrostatic interactions, forming abundant SERS hot spots. The MXene/ AuNR SERS substrate exhibits high sensitivity and excellent reproducibility in the determination of common organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…This nanocomposed substrate could also increase the detection limits for organic contaminants such as thiram and diquat to 1 × 10 −10 and 1 × 10 −8 m, respectively. [108] Therefore, MXenes with nano composites act as efficient SERS detection substrates in various applications including biomedical imaging, high sensitivity environmental analysis, and food safety monitoring.…”
Section: Plasmonic Propertiesmentioning
confidence: 99%
“…This nanocomposed substrate could also increase the detection limits for organic contaminants such as thiram and diquat to 1 × 10 −10 and 1 × 10 −8 m, respectively. [108] Therefore, MXenes with nano composites act as efficient SERS detection substrates in various applications including biomedical imaging, high sensitivity environmental analysis, and food safety monitoring.…”
Section: Plasmonic Propertiesmentioning
confidence: 99%
“…It has been reported that the Raman enhancement of dyes is solely dependent on the thickness of the MXene film, as well as the type of supporting substrate, like glass, Si or filter paper. [10][11][12][13]15,33 Previously, we have shown that SERS enhancement of the Ti 3 C 2 T x thin film on SiO 2 /Si exhibited a higher EF (5 Â 10 5 ; l 0 = 514 nm; EF based on both the EM and interband transition/ charge transfer (CT) mechanism of the enhancement) than those with a thicker and more uniform coating of Ti 3 C 2 T x film on SiO 2 / Si by spray-coating. 11 However, increasing the thickness of the Ti 3 C 2 T x film leads to a decreased SPR sensitivity as well as the Raman enhancement of dyes adsorbed on Ti 3 C 2 T x on the Si/SiO 2 substrate.…”
Section: Communicationmentioning
confidence: 99%
“…6,[10][11][12][13][14][15] The Raman enhancement mechanism from the monolayers of the 2D material is believed to be mainly CM. 2,5,16 It has been reported that another family of 2D materials, transition metal carbides and nitrides (MXenes) can be used as SERS substrates [10][11][12][13]15 and for other applications. [17][18][19] Both the structure and electronic properties of MXene-Ti 3 C 2 T x were largely affected by the functional groups on the MXenes where X = -F, -O and -OH.…”
mentioning
confidence: 99%
“…Retrosynthesis and optimization are the Robotic Scientist's creative endeavors. The data of the target Au nanocrystals (such as LSPR as 808 ± 10 nm, 780 ± 10 nm, and 633 ± 10 nm), which are commonly used in biotechnology and information technology (for example, HIV drug delivery 16 , surface-enhanced Raman scattering 17 , wireless neuromodulation 18 , and sensing 19,20 ), are extracted from the genome for further retrosynthesis study. Using 808 ± 10 nm as an example, 99 samples are selected from previous single-, double-, and three-factor experiments as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%